The single nucleotide polymorphism rs2305957 G/A is not associated with recurrent pregnancy loss - Sharif, Fadel A.; Ashour, Mohammed (International Journal of Research in Medical Sciences, 2017)
Background: This study was conducted in order to investigate the association between the single nucleotide polymorphism (SNP) rs2305957 G/A and recurrent pregnancy loss (RPL) in a group of Palestinian women residing in Gaza strip. Methods: A retrospective case-control study was carried out during the period (May to August, 2015). A total of 380 females, 190 RPL patients and 190 control women without previous history of RPL, aged 20–35 years were included in the study. The SNP was analyzed by tetra-primer amplification refractory mutation system PCR (T-ARMS-PCR). Results: No statistically significant difference existed between RPL cases and controls in terms of the allelic and genotypic distribution of rs2305957 G/A. Conclusions: SNP rs2305957 G/A does not represent a risk factor for RPL in the investigated population.